Analysis of Leading Economic Sector in South Jakarta Administrative City - Mega Putri Yunita; Yesi Dewitasari; Septa Riadi (Majalah Ilmiah Bijak, 2021)
This study aims to determine the basic and non-basic sectors in the city of South Jakarta Administration, then to find out what sectors are the concentration and specialization of economic growth in the Administrative City of South Jakarta and to determine the level of economic growth through the leading sectors in the city of South Jakarta Administration. The method used in this research is descriptive qualitative research. Data collection techniques were carried out by a study of literature. Based on the Location Quotient (LQ) analysis, Specialization Index (IS) and Shift Share Analysis (SSA), the results of this study show that in sectors that have LQ> 1, the IS value is positive and the SSA component is also positive , namely the information and communication sector.